Hyperbaric Oxygen Therapy Increases Brain-Derived Neurotrophic Factor as well as Decreases Systemic Immune-Inflammatory Index and Systemic Inflammatory Response Index in Autism Spectrum Disorder - Verna Biutifasari; Ni Komang Sri Dewi Untari; Pramita Anindya Nugraheni; Ronald Pratama Adiwinoto; Djatiwidodo Edi Pratiknya; Vendra Setiawan; Hartono Kahar; Betty Agustina Tambunan (Indonesian Biomedical Journal)
BACKGROUND: Neuroinflammation and immune dysregulation are frequently viewed as contributing factors of autism spectrum disorder (ASD). Brain-derived neurotrophic factor (BDNF) is involved in the maintenance of neuron viability, as well as in neuron differentiation. Meanwhile, Systemic Immune-Inflammatory Index (SII) and Systemic Inflammatory Response Index (SIRI) are basic hematological indices used to assess inflammation and immune status. Hyperbaric oxygen (HBO) is known to enhance cerebral blood flow and reduce inflammation, however, not many studies have observed the its effect on BDNF level, SII, and SIRI in ASD subjects; therefore, this study was performed.